Pengaruh Tata Kelola Perusahaan Dan Budaya Organisasi Terhadap Kualitas Laporan Keuangan Cv. Kadinya Citra Boga Periode 2015-2020 - Cahyadi, Putri Marlena; Kuraesin, Arlis Dewi (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2022)
The problem in this study is the influence of corporate governance and organizational culture on the quality of the financial statements of CV. Kadinya Citra Boga and aims to determine the effect of corporate governance and organizational culture on the quality of the financial statements of CV. Kadinya Citra Catering. This type of research is quantitative by using primary data obtained from the questionnaire results. The population in this study was 63 people, while the sample used was 63 respondents, the results of the determination of the sample used a saturated sample. The data analysis technique used in this study used the questionnaire method, for data processing using SPSS version 26 statistical software. The results of the study indicate that corporate governance has an effect on the quality of financial reports. Meanwhile, the organizational culture variable also has a significant effect on the quality of financial reports. Simultaneously, corporate governance and organizational culture have a significant effect on the quality of financial reports. This is the same as the research conducted by Suhaini in 2018 with the title The influence of corporate governance and organizational culture on the quality of financial reports with the result that corporate governance and organizational culture have a significant effect on the quality of financial reports. Therefore, companies must pay attention to corporate governance issues so that they can be improved and the organizational culture is made comfortable and healthy to improve the quality of financial reports.